Optimasi Formula Facial Wash Gell Antipolutan Ekstrak Bunga Rosella Ungu (Hibiscuss sabdariffa L. Var. Roselindo2) - Anisa Fitri, Hidayah; Falahdin, Fadita Iza; Astuti, Ika Yuni (Farmasains : Jurnal Ilmiah Ilmu Kefarmasian, 2025)
Exposure to Particulate Matter (PM) and other airborne pollutants can lead to various skin issues. The anthocyanin compounds in purple roselle flower extract exhibit antipollution activity, making the extract a promising candidate for the development of a facial wash gel formulation, optimised with carbopol 940 and triethanolamine (TEA). These two ingredients were selected due to their influence on the physical properties of the formulation, which is expected to help maintain the physicochemical stability of anthocyanins. This study aimed to determine the optimal concentrations of these components as gel base-forming agents, such as viscosity, pH, and spreadability. The optimum formula was designed using Design Expert 13 software with a Simple Lattice Design (SLD) model, while statistical analyses were conducted using one-way ANOVA and T-test to verify the predicted and actual optimum formula. The physical evaluation results confirmed that the optimum formula met the required viscosity (3826±28.67 cPs), dispersibility (6.07±0.45 cm), and exhibited an acidic pH (6.53±0.07) suitable for a facial cleansing gel. Based on the conducted tests and analyses, the optimum formula contained 2% carbopol 940 and 2% TEA, with a desirability value of 0.993. Verification testing indicated no significant differences between the predicted and actual optimum formula.